Higher-order dynamic delay differential equations on time scales - Su, H.; Liu, Lishan; Wang, X. (Hindawi Publishing Corporation, 2012)
We study the existence of positive solutions for the nonlinear four-point singular boundary value problem with higher-order p -Laplacian dynamic delay differential equations on time scales, subject to some boundary conditions. By using the fixed-point index theory, the existence of positive solution and many positive solutions for nonlinear four-point singular boundary value problem with p -Laplacian operator are obtained. © 2012 Hua Su et al.